A Review - Does Low Magnitude High-Frequency Vibration (LMHFV)Worth for Fracture Recovery Compared with Pulsed Electromagnetic Field (PEMF) Based Magnetotherapy Method? Evi Suaebah, Rohim Aminullah Firdaus, Muhimmatul Khoiro - Evi Suaebah Evi Suaebah; Rohim Aminullah Firdaus Rohim Aminullah Firdaus; Muhimmatul Khoiro Muhimmatul Khoiro (Jurnal Fisika dan Aplikasinya, 2023)
The subject of electromagnetic fields is widespread today, including in the medical world. One of them is therapy in fracture healing using the Pulsed Electromagnetic Field (PEMF) method by utilizing a magnetic field. Fracture healing using the magnetic field method utilizes the Helmholtz coil, which is influenced by the current and the amount of turns flowing in the magnetic field. This study conducted a literature study on fracture healing using the PEMF and the LMHFV methods. A comparison of these two methods will show different healing effects. From the studies, we can conclude which way has the most advantage in healing. A faster rehabilitation process will have an impact on reducing implant failure. In contrast, Applying the LMHFV method to bone fractures gives more significant and faster results in bone formation in the damaged part, and the healing process is owned faster. From these two methods, it can be concluded that the LMHFV method provides a similar healing effect than the PEMF method. Applying the LMHFV and PEMF method to bone fractures gives more significant and faster results in bone formation in the damaged part. In addition, the healing process is owned faster.